Simulation in healthcare in the realm of Education 4.0 - Zaleha Abdullah Mahdy; Muhammad Maaya; Ixora Kamisan Atan; Azlan Helmy Abd Samat; Mohd Hisham Mohd Isa; Ismail Mohd Saiboon (Penerbit Universiti Kebangsaan Malaysia, 2020)
The advent of Education 4.0, in parallel with Industrial Revolution (IR) 4.0, has translated into an evolution in healthcare education. Simultaneously, as a result of concerns in doctors’ competency and patient safety, simulation shot into center-stage in the field of healthcare education. Generally, there are five modalities in healthcare education, namely role-play (verbal), standardized patient, part-task trainer, computer or screen-based simulation, and electronic patients including virtual reality. Dissecting the nine principles of Education 4.0, this article reviews the relevance and role of the five different modalities of simulation in easing healthcare education into the mold of Education 4.0.